Prognostic value of lymph node micrometastasis in esophageal cancer: A systematic review and meta-analysis - Yang, Jing; Liu, Qianqian; Bai, Yuping; Zhao, Haitong; He, Tingting; Zhao, Ziru; Huang, Min; Jiang, Mengyuan; Zhang, Rui; Zhang, Min (Frontiers in Oncology, 2023)
Objective Whether lymph node micrometastasis (LNM) increases the risk in esophageal cancer patients remains controversial. We conducted a systematic review and meta-analysis to explore the prognosis value of LNM in esophageal cancer patients. Methods Two reviewers independently searched electronic databases, including PubMed, Embase, and the Cochrane Library, for eligible citations until February 2022. We calculated pooled estimates of the hazards ratio with a random-effects model. The certainty of evidence was determined by the Grade of Recommendations Assessment, Development, and Evaluation (GRADE) method. A sensitivity analysis was performed to assess the stability. Publication bias was assessed using funnel plots and Egger’s test. We also performed subgroup analysis to explore the source of heterogeneity. Results A total of 16 studies, with 1,652 patients, were included. The overall survival (OS) was significantly increased with LNM negativity compared with LNM positivity (HR 1.95; 95% CI, 1.53–2.49; P < 0.001; I2 = 0.0%, P = 0.930; certainty of evidence: low). Relapse-free survival (RFS) was significantly increased with LNM negativity compared with LNM positivity (HR 3.39; 95% CI, 1.87–6.16; P < 0.001; I2 = 50.18%, P = 0.060; certainty of evidence: moderate). No significant difference was observed in recurrence between the two groups (certainty of evidence: low). Sensitivity analysis revealed a stable trend. In addition, the funnel plot and Egger’s test did not show significant publication bias. Conclusion LNM positivity worsens the prognosis in esophageal cancer, and the evidence for RFS is moderate. Future relevant high-quality studies are warranted to validate our results further and provide a reference for guidelines. Systematic review registration https://www.crd.york.ac.uk/prospero, identifier (CRD42022321768).